Perceptions of Malaysian school and university ESL instructors on writing assessment. - Mukundan, Jayakaran; Ahour, Touran (2009)
This study is an attempt to find out the attitudes of writing teachers and lecturers towards the assessment of writing. For this purpose, a survey using questionnaire and semi-structured interview was conducted among ESL (English as A Second Language) university lecturers and school teachers and the data were analyzed descriptively and qualitatively. The results indicate that university lecturers (UL) prefer impressionistic scoring while school teachers (ST) prefer criterion-based scoring. Both groups express their preferences for explicit instruction of the evaluation criteria as well as in identifying students’ weaknesses and strengths. Unlike the common belief that grammar, vocabulary, and mechanics are the most essential criteria in scoring, the results show that fluency is more important than accuracy. It is also found that years of teaching experience are not an influential factor in their responses.